(3CeGdj GdqRLGLjs - (3YHO GdQMef Hf ESMGb GdfgGhfOj GdRLGLj, CHh GdbGSe,J (B337 (3g` s
(3ChdgG (B:s
(3bGd CHhGdbGSe QMeg Gddg Qhi Yf GdTYHj Cfg bGd(B: (3bGd YHOGddg Hf eSYhO QMeg Gddg aj bhdg YR hLd(B: "(3Ef EHQGgje cGf CekI bGfJkG ddg MfjakG(B" (3bGd GdCeI(B: (3GdQLd GdeYde ddNjQ s
(3BNQgG (B:s
(3aGdJaJ HTGQ Edi bGFOg, abGd dg(B: (3HFSJ GdOGQ gPg GdOGQ, aj cGfh GdKGfj JeJ CeGdj GdqRLGLj s
(3HBNQgG Jedc HJGQjN (B778(3g``s
(3JHUQI GdYfhGf (B:s
(3TQM hGedGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B124s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B57 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B164s
Keywords: (3GdCOHs